Intergenerational risk sharing by means of pay-as-you-go programs: an investigation of alternative mechanisms - Øystein Thøgersen (Center for Economic Studies and ifo Institute (CESifo), 2006)
A pay-as-you-go (paygo) pension program may provide intergenerational pooling of risks to individuals' labor and capital income over the life cycle. By means of a model that provides illuminating closed form solutions, we demonstrate that the magnitude of the optimal paygo program and the nature of the underlying risk sharing effects are very sensitive to the chosen combination of risk concepts and stochastic specification of long run aggregate wage income growth. In an additive way we distinguish between the pooling of wage and capital risks within periods and two different intertemporal risk sharing mechanisms. For realistic parameter values, the magnitude of the optimal paygo program is largest when wage shocks are not permanent and individuals in any generation are considered from a pre-birth perspective, i.e. a rawlsian risk sharing perspective is adopted.
Keywords: H55; D91; E32; G11; 330; Gesetzliche Rentenversicherung; Risiko; Overlapping Generations; Alterssicherung; Theorie